(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Academic vocabulary is a critical component of English Language Learners’ (ELLs) success in K–12 classrooms, as it directly influences comprehension, participation, and overall academic achievement across content areas. This article explores the challenges ELLs face in acquiring academic vocabulary and emphasizes the importance of explicit and systematic instruction alongside opportunities for incidental learning. Drawing on research in second language acquisition, including Krashen’s monitor model and the benefits of extensive reading, as well as Chomsky’s Universal Grammar, the study highlights how a language-rich, supportive classroom environment fosters vocabulary development. Practical strategies for teaching academic vocabulary—such as contextualized instruction, repeated exposure, and active use in speaking and writing—are discussed. The findings suggest that integrating structured vocabulary teaching with communicative and content-based activities enhances linguistic proficiency, boosts learner confidence, and supports cognitive and academic growth, ultimately enabling ELLs to succeed in both language and subject-area learning.